Epistemological Differences in Islam: Traditional, Rational, and Sufistic Approaches - Bilal Indra Putra; Husni Husni; Sri Wahyuni (Publikasi Indonesia, 2025)
Epistemology in Islam is not singular, but rather a development in various schools of thought that reflects different approaches to sources and methods of acquiring knowledge. This journal examines three main approaches in Islamic epistemology, namely: traditional (naqli), rational (aqli), and sufistic (dzauqi). By examining the various central figures and the arguments they developed, this journal aims to show the dynamics of epistemological thought in the Islamic tradition and the impact it has on the development of science and spirituality of Muslims.